A human surfactant B deficiency air-liquid interface cell culture model suitable for gene therapy applications - Munis, AM; Hyde, SC; Gill, DR (Elsevier, 2020)
Surfactant protein B (SPB) deficiency is a severe monogenic interstitial lung disorder that leads to loss of life in infants as a result of alveolar collapse and respiratory distress syndrome. The development and assessment of curative therapies for the deficiency are limited by the general lack of well-characterized and physiologically relevant in vitro models of human lung parenchyma. Here, we describe a new human surfactant air-liquid interface (SALI) culture model based on H441 cells, which successfully recapitulates the key characteristics of human alveolar cells in primary culture as evidenced by RNA and protein expression of alveolar cell markers. SALI cultures were able to develop stratified cellular layers with functional barrier properties that are stable for at least 28 days after air-lift. A SFTPB knockout model of SPB deficiency was generated via gene editing of SALI cultures. The SFTPB-edited SALI cultures lost expression of SPB completely and showed weaker functional barrier properties. We were able to correct this phenotype via delivery of a lentiviral vector pseudotyped with Sendai virus glycoproteins F/HN expressing SPB. We believe that SALI cultures can serve as an important in vitro research tool to study human alveolar epithelium, especially for the development of advanced therapy medicinal products targeting monogenic disorders.